#TITLE_ALTERNATIVE# - ALODIA BAWONO (NIM: 22014319), ALMIRA
A potential pay zone with the log resistivity interpretation indicates high water saturation but confirmed afterward to have hydrocarbon pay from well testing result was identified at some certain intervals. The aim of this thesis was to identify, predict and determine the cause factor of low resistivity pay zone (LRPZ) in reservoir of Talang Akar Formation in Jambi subbasin and Palembang subbasin within South Sumatra basin to determine the appropriate petrophysical properties. The methods used in this study were cutting analysis, log analysis, core analysis, cross plot analysis and well test data analaysis to identify and predict the low resistivity pay zone. Shaly sand analysis model was also used to determine the petrophysical properties LRPZ. The results of this study show the identification of 4 LRPZs with well test result and predict 15 LRPZs without well test result from 4 wells served as subjects in a study design. The 19 LRPZs were clustered into two electrofacies clusters that is Yellow-Electrofacies and Red-Electrofacies. Based on core data analysis, both of these electrofacies belong to fluvial channel facies. Yellow-Electrofacies (Fluvial Channel A/FCA) covers LRPZ within wells subject study in Jambi Subbasin. The cause factor of LRPZ is the presence of superficial microporosity. The average effective porosity is 0,21 decp and hydrocarbon saturation is 20-30%. Red-Electrofacies (Fluvial Channel B/FCB) covers low resistivity pay zone within wells subject study in Palembang Subbasin. The cause factors of LRPZ are the presence superficial microporosity and the presence of conductive minerals. The average effective porosity is 0,21 decp and hydrocarbon saturation is 20-30%. The research shows that Talang Akar Formatin in South Sumatra Basin has hydrocarbon potential from Low Resistivity Pay Zone. The identification and prediction of LRPZ using cut-offfrom cross plot method is applicable in Talang Akar Formation within Jambi Subbasin and Palembang Subbasin.